Design of slow sand filter as a rainwater treatment technique for residential applications - Cabungcal, Rodgie Ello B.
Water scarcity is a problem in the Philippines especially in the domestic sector where only 7.27 percent of the total water supply is being allocated. Consequently, there is a need to find alternative water sources that will help lessen the problem. One solution is the use of rainwater which is a good alternative since the country has high amount of rainfall. But there is uncertainty on the quality of rainwater. It still poses health risks and danger on possible users. The main purpose of the study is to provide design guidelines of slow sand filter for possible implementation. It aimed to make an actual slow sand filter and to retrofit the selected study area. It also aimed to characterize the collected rainwater before treatment to know its possible use. The design of the slow sand filter was based from different studies conducted about the said filter. Specific ratio of depths and grain sizes of sand and gravel were designed to meet the recommended values. It was assessed that a slow sand filter is a cheap and economical but efficient filter. The model house was also assessed for retrofitting. The roofing system especially the gutter and pipes are replaced and cleaned since they are non- functional anymore. The collected rainwater was also characterized using different methods depending on the parameters. It was characterized based from the following parameters: pH, TSS, TDS, Alkalinity, Sulfate and E. coli. It was found out that the collected rainwater is not suitable for either potable or non-potable applications so there is a need to use a treatment technique to improve its quality. In this case, a slow sand filter is found to be a good treatment technique.